Validation of a comprehensive skin risk assessment and management instrument for hospitalized neonatal patients - Tanty Harjati; Yeni Rustina; Happy Hayati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Health services have increasingly shifted their focus from treating skin diseases and skin injuries to emphasizing preventive efforts through routine assessments. Various treatment equipment and neonatal conditions such as infant weight, gestational age, clinical status, and underlying diseases have been shown to have a strong association with the risk of skin injury. Early detection using valid assessment instruments is therefore essential in neonate care. Purpose: To determine differences in skin injury risk levels in neonates using the SRAMT and NSRAS Plus instruments, and to examine the relationship between gestational age and birth weight with the risk of skin injury. Method: This short cohort design involving a total of 66 neonates, divided into an exposed group and an unexposed group (historical control). Skin injury risk assessments were conducted using the SRAMT and NSRAS Plus instruments. Data were analyzed by comparing the first and last assessments within the exposed group, comparing exposed and unexposed groups, and testing correlations between gestational age, birth weight, and skin injury risk. Results: The findings showed significant differences in skin injury risk levels between the first and last assessments in the exposed group (p = 0.001). There were also significant differences in skin injury risk levels between the exposed and unexposed groups (p = 0.001). However, no significant correlation was found between gestational age (p = 0.446) or birth weight (p = 0.821) and the level of skin injury risk. Conclusion: The study concludes that preventive monitoring using the SRAMT and NSRAS Plus instruments effectively identifies changes in skin injury risk in neonates. Gestational age and birth weight were not found to have a significant relationship with the level of skin injury risk. Suggestion: Researchers and health professionals are encouraged to integrate nurses’ knowledge regarding factors contributing to skin injury and to consistently re-monitor neonates using the SRAMT instrument. Modification of the instrument is also suggested to align it with current neonatal service conditions in Indonesia, enabling more effective prevention of skin injury, especially among preterm infants.